ENHANCING THE CAPACITY OF ORGANIZATIONS AND HIGHER EDUCATION INSTITUTIONS (HEIS) IN INCREASING GRADUATES EMPLOYABILITY SKILLS (Proceedings of the International Conference on Education, 2018)
This paper analyzed the perceptions of Graduates, Higher Education Institutions (HEIs) and Employers on Graduates Employability in Bangladesh. By using Quantitative Methodology, the study found that there is a significant perception gap between Employers and Graduates as Graduates strongly believe that scoring higher CGPA increases the chance of securing a job in the competitive labor market, on the other hand Employers give top most priority on ‘Integrity’ and ‘Communication Skills’ and advised that CGPA is used mostly for job applications screening purpose. Therefore HEIs should include ‘Employability Skills’ in the curriculum and assessment. Though few HEIs have introduced Outcome Based Evaluation (OBE), however these are yet to contribute in Employability Skills Development. The Existing Curriculum is not Employability Skills focused, so Employers and HEIs should establish a collaborative strategy for developing Employability Skills that will eventually develop efficient Human Resources.
Keywords: Employability Skills; CGPA; Employers; HEIs; Graduates